Pigeons Show Metamemory by Requesting Reduced Working Memory Loads - Sumie Iwasaki; Hika Kuroshima; Kazuo Fujita (Animal Behavior and Cognition, 2019)
Even though many studies have demonstrated that pigeons and humans share various properties of memory systems, pigeons have shown only weak evidence of metamemory ability, for example during delayed matching-to-sample. We suspect that this task might be too demanding to allow metamemory processing within pigeons’ working memory. Here, we describe our studies in which pigeons have shown metamemory during a task requiring reduced working memory load, a reference memory task. Pigeons solved a simultaneous chaining task, and they were sometimes given the opportunity to ask for ‘‘hints’’ about the next correct response in a sequence before or during the task. Some pigeons’ hint-seeking behavior varied according to their reference memory states or knowledge states, suggesting that they used metamemory when engaged in a reduced working memory load task. We propose that metamemory ability is dependent on working memory capacity, and that it is important to use suitable cognitive tasks for evaluate metamemory abilities in diverse species.